Pemberdayaan Sumberdaya Alam Desa Sudajaya Girang untuk Pembangunan Kampung Flori - Muhammad Gian Gianggi Pratama; Diah Ayu Puji Lestari; Gunawan Santosa (Jurnal Pusat Inovasi Masyarakat (PIM), 2020)
Sudajaya Girang Village has potential in developing the agricultural sector, however, in this case still a need for activities that support the development of local village potential through mapping the local potential of the village and through SUJI activities (Socialization of the Kampung Flori Initiation Efforts) and GERBERA (Movement for Learning About Nature) which held at the local elementary and middle school. The purpose of this activity is to help the people of the village of Sudajaya Girang in mapping the local potential of the village and training in making vertical gardens, besides this activity also socializes the importance of protecting the environment for elementary and junior high school students. Visualization of the potential of Sudajaya Girang Village in RW 03 and RW 04 regarding the location of gardens, cultivation fields and centers of cut flower crafts and ornamental plants. The method used interviews, socialization, practice and also maping locations using GPS. Based on the interview survey that has been done shows that the enthusiasm of the community is high regarding the development of farmer groups, but not yet supported by adequate human resources, so there is a need for further programs to help prepare resources community power in starting entrepreneurship in the field of flori. The success of the socialization activities to elementary and junior high school students related to the importance of protecting the environment can be seen from the enthusiasm of the students in participating in a range of programs such as getting to know the typical flora and fauna types of the village, as well as being able to sustainably utilize the typical flora of the village for making a herbarium which in the future is expected to become learning activities for entrepreneur. Keywords: : Cut flowers, suji plants, stringing flower